LSD1 co-repressor Rcor2 orchestrates neurogenesis in the developing mouse brain - Wang, Yixuan (Nat Commun, 2016)
Epigenetic regulatory complexes play key roles in the modulation of transcriptional regulation underlying neural stem cell (NSC) proliferation and progeny specification. How specific cofactors guide histone demethylase LSD1/KDM1A complex to regulate distinct NSC-related gene activation and repression in cortical neurogenesis remains unclear. Here we demonstrate that Rcor2, a co-repressor of LSD1, is mainly expressed in the central nervous system (CNS) and plays a key role in epigenetic regulation of cortical development. Depletion of Rcor2 results in reduced NPC proliferation, neuron population, neocortex thickness and brain size. We find that Rcor2 directly targets Dlx2 and Shh, and represses their expressions in developing neocortex. In addition, inhibition of Shh signals rescues the neurogenesis defects caused by Rcor2 depletion both in vivo and in vitro. Hence, our findings suggest that co-repressor Rcor2 is critical for cortical development by repressing Shh signalling pathway in dorsal telencephalon.